Berkley forum - Berkley Center for Religion, Peace, and World Affairs (2007)
The Berkley Forum is an online platform for public scholarship and informed commentary at the intersection of religion and world affairs. Each series of essays brings together a diversity of experts to engage in rigorous debate on a religious or ethical issue of global significance